1996
DOI: 10.1042/cs0910233
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Iron Deficiency in Rats: Mechanical and Electrophysiological Alterations in the Cardiac Muscle

Abstract: 1. Our aim was to investigate the effect of experimental iron deficiency on cardiac functional properties. We recorded ventricular isometric twitch, action potentials and the L-type Ca2+ current in isolate ventricular myocytes from iron-deficient rats and control rats. 2. Twitch tension and maximal rates of tension activation and relaxation were reduced in iron-deficient compared with control rats, whereas twitch duration was prolonged. Isoproterenol (10-(6) mol/l) augmented tension in iron-deficient rats (P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Experimental studies have shown that ID induced cardiac dysfunction13 and cardiac hypertrophy, characterized by aberrant mitochondrial and irregular sarcomere organization 14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have shown that ID induced cardiac dysfunction13 and cardiac hypertrophy, characterized by aberrant mitochondrial and irregular sarcomere organization 14…”
Section: Discussionmentioning
confidence: 99%
“…12 Despite the crucial role of iron in the physiology of cardiovascular system, this element remains understudied outside of the erythropoietic system. Experimental studies have shown that ID induced cardiac dysfunction 13 and cardiac hypertrophy, characterized by aberrant mitochondrial and irregular sarcomere organization. 14 Given previous evidence, it seems plausible to speculate that ID may play a causative role in the pathophysiology of HF beyond anaemia.…”
Section: Discussionmentioning
confidence: 99%
“…A previous investigation [20] has suggested that altered myocardial function develops in iron-deficient rats with changes in ventricular contractility, maximal rates of contraction and relaxation, action potentials and L-type Ca 2+ currents. In addition, the twitch duration was prolonged similar to that observed in diabetes and heart failure [20]. These electrophysiological changes may contribute to depressed cardiac function with iron deficiency.…”
Section: Figure 4 Effect Of Dietary Iron Deficiency On Cardiac Proteimentioning
confidence: 98%
“…In vitro studies suggest that iron deficiency directly impairs myocyte mechanical function 71 and that iron deficiency anemia induces LVH 72 characterized by myocyte hypertrophy and hypercellularity. 73 Anemia also may exacerbate heart failure through a series of downstream events in which tissue hypoxia and nitric oxide release cause peripheral vasodilation and blood pressure decreases.…”
Section: Role Of Ckd-associated Biochemical Abnormalities In the Pathmentioning
confidence: 99%